RESEARCH AND ANALYSIS OF INDICATORS ECOFRIENDLINESS OF WORKING ENVIRONMENT: Array - , О. Ф. (Municipal economy of cities. Series: «Economy science», 2018)
The current stage of production development is associated not only with the widespread usage of technical innovations in various fields of the economy, but also with the need to change the approach to assessing their impact on a human and an environment. Changing the approach means introducing new criteria for assessment of safety of a production process. These criteria include an ecofriendliness of working environment. The complexity of using this criterion lies in its integrity, because in the process of evaluation it is necessary to take into account heterogeneous indicators, the list of which is non-constant and depends on the opinion of the researcher. Literary search and analysis showed that for today the most informative indicators of ecofriendliness of working environment are the following: ecofriendliness of materials from which elements of the workplace are made; ways of creating and maintaining working conditions indoors; interior of a working room; features of an enterprise exterior. In this paper, all listed ecofriendliness indicators were researched and their role in the evaluation system were determined. Along with this, it was established that the list lacks ecological needs indicator (or ecological requests) of an employee. The need for its introduction into the system of ecofriendliness assessment is determined the transition of production to a new level of functioning, which involves usage of innovative development strategies. One of these strategies is the search of approaches to more efficient using of human resources, which envisages a revision of the issue about employee’s individual needs, because today they include not only social and psychological aspects, but also its ecological requests. The definition of ecofriendliness of working environment allows: 1) to minimize the negative impact on the health of workers of ecological negative factors of the working environment by means of using the most safe materials and, possibly, by a partial reorganization of the enterprise structure; 2) to increase the level of psychological comfort of workers through the realization of their needs and to create a sense of maximum safety in the workplace; 3) to improve the financial and economic performance of the enterprise because of increased productivity and motivation of employees. Keywords: safety, health, ecofriendliness of working environment, ecological needs.